Handbook of cartography - De Lima, Marina (Callisto Reference, 2015)
"The space where natural systems and social systems interact is called terrestrial space. Cartography is a means to understand these intricate systems, their interaction and evolution. Hence, cartography has acquired a significant place in the modern scenario. This book provides an overview of the activities which state the significance of cartography in the perception and organization of the territory into distinct areas. Studying the past or understanding the present, cartography has always been a tool to explore all themes of knowledge".